“Authentic reading resources in the learning process of English language in the students of Tercero de Bachillerato “A” at “Amelia Gallegos Diaz” high school in the city of Riobamba, Chimborazo Province in the academic year 2015-2016”. - Gomez Minta, Mery Susana (2016)
This research was developed in the third year of Bachillerato “A” in the school “Amelia Gallegos Diaz” in Riobamba City. The present study focuses on the different authentic reading resources that should be used for teaching and learning, after observation the main problem is that students usually do not use authentic reading resources; this requires constant use outside and inside the classroom. The qualitative method employed was ethnographic and the diagnostic level, which allowed us to collect data, those respond to the goals that were proposed. The information was collect through two observation guides for four weeks. Through this research and the verification of the established goals, a positive result was obtained there is a change in the teachers and students attitude, in the use of authentic reading resources in real learning situations. In conclusion, the use of authentic that the educator commonly uses in class such as short stories, books and songs is very limited. That has caused frustration, disconcerted and low motivation in students to learn and improve their English language skills.